(3eaJGM OGQ GdSYGOIs - (3eMeO Hf CHj HcQ Hf CjhH Hf SYO GdRQYj GdOeTbj, CHh YHO Gddg, TeS GdOjf,J (B751 (3g` s ((3YHO Gddg Hf eMeO Hf YHO GdMb Hf YHO GdCYdi GdeGdci s)
(3ChdgG (B:s
(3aUd hai gPg GdBdGJ eBQH CNQi hefGaY Shi efaYI GdcdGe aai GdMfLQI eSdc GdfSje GdHGQO s
(3BNQgG (B:s
(3hEf TFJ EbJHSJ efg eYQaI GdWjQI hGdaGd hGdQLR hGdaQb Hjf UMjM Pdc hHGWdg fLR GdcJGH HMeO Gddg JYGdi hYhfg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B56 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B106s
Keywords: (3GdJUha hGdBOGH GdTQYjIs